2021
DOI: 10.1051/0004-6361/202039159
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic signatures on mixed-mode frequencies

Abstract: Context. The discovery of moderate differential rotation between the core and the envelope of evolved solar-like stars could be the signature of a strong magnetic field trapped inside the radiative interior. The population of intermediate-mass red giants presenting surprisingly low-amplitude mixed modes (i.e. oscillation modes that behave as acoustic modes in their external envelope and as gravity modes in their core) could also arise from the effect of an internal magnetic field. Indeed, stars more massive th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 160 publications
2
50
0
Order By: Relevance
“…There is also the potential to look at the timing of the extra mixing, as well as mixing rate as a function of time. Further, it may be possible to investigate whether mixing can be connected to the sorts of asteroseismic diagnostics that probe the interior structure of a star, including its density profile (Kjeldsen & Bedding 1995), chemical discontinuities (Verma et al 2017), internal rotation (Gehan et al 2018), and magnetic fields (Bugnet et al 2021).…”
Section: One-dimensional Stellar Evolution Models Suggestmentioning
confidence: 99%
“…There is also the potential to look at the timing of the extra mixing, as well as mixing rate as a function of time. Further, it may be possible to investigate whether mixing can be connected to the sorts of asteroseismic diagnostics that probe the interior structure of a star, including its density profile (Kjeldsen & Bedding 1995), chemical discontinuities (Verma et al 2017), internal rotation (Gehan et al 2018), and magnetic fields (Bugnet et al 2021).…”
Section: One-dimensional Stellar Evolution Models Suggestmentioning
confidence: 99%
“…Van Beeck et al (2020) made a systematic exploration of this magnetic signature along the evolution of intermediatemass pulsating γ Doradus (γ Dor hereafter) and slowly pulsating B (SPB) stars and showed that the magnetic signatures differ appreciably from those due to rotation alone. They found that these signatures are measurable for dipolar gravity mode oscillations in terminal-age main-sequence (TAMS) stars for a magnetic field with a near-core strength larger than 10 5 G. Next, Bugnet et al (2021) and Loi (2021) studied the perturbation of mixed gravito-acoustic modes propagating in evolved low-and intermediate-mass stars by axisymmetric and non-axisymmetric inclined mixed dipolar fossil fields, respectively. They identified asymmetries in the frequency splittings induced by the field.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, the possibility to detect magnetic fields through their effect on the oscillation frequencies is under investigation (see e.g. Bugnet et al 2021). Awaiting observational evidence, theoretical work strongly supports the presence of magnetic fields in stars that possess a convective core (MS stars with M 1.2 M ).…”
Section: Introductionmentioning
confidence: 99%